- - Twycross, Robert (Acta Bioethica, 2000)
After summarizing the historical background and development of former hospices, the author analyses the philosophy that has inspired Palliative Medicine from its selfsame origins up to the present in different countries in the world. The apparent paradox that supposes to find life and joy amidst death and suffering explains the peculiar ethos that guides teamwork, an ethos grounded on practical humane compassion. Despite emphasizing that Palliative Medicine ethics is not different from the one of general medicine, the writer pauses to consider some of the most relevant ethical dilemmas related to accompaniment of dying patients, such as truth disclosure, identification of appropriate treatments, nutrition and hydration supply, and the debate on euthanasia and physician assisted suicide. The connecting theme of the work is the necessity of providing terminal patients with an interdisciplinary professional accompaniment -highly qualified and personalized- intended to consider the totality of patients' and families' human dimensions.